EMPATI INTERAKTIF KELUARGA POLIGAMI - , zULIKA; , Prof. Dr. Tina Afiatin ([Yogyakarta] : Universitas Gadjah Mada, 2013)
So far, polygamy has obtained pro and contra discussion. Nevertheless, there are some polygamy families maintaining their marriages. There are some reasons for these polygamy families, some of wives on these families chose another wife for her husband or willingly being the second or the third wives. In order to minimize serious conflicts on polygamy family are needed good interaction abilities toward each family members. One of interaction abilities is empathy ability to maintain a good relation. This study is motivated by researcherâs interest in interactive empathy in polygamy family. This study used case study method between two different cases on polygamy families: polygamy families having serious family conflicts and few conflicts. Data collection is used by interview (in depth interview) and observation. Total respondents in this study are seven (two polygamy husbands, two wives, one child, and two knowing informants) which are from two different polygamy families. This study result disclosed that two polygamy husbands had similar intention on deciding to have polygamy: sex, in which started by conflicts in the households. The wives of them, at first, showed rejection attitudes but then changed their attitudes to tolerate because of harmony value in Java culture. Empathies in these two families (called AN and SR) have different process. Interactive empathy in AN polygamy family has been built from its polygamy marriage by forgiving her husband because of similar experiences of the first and second wives (having marriage after got pregnant). Thus, interactive empathy has been built between the first wife and second wife. While, interactive empathy in SR polygamy family is very conspicuous emerging when SR admitted the second wife to did treesomesex with two men in order to release her grudge toward the first wife because of her disappointment for being second wife, then built interactive empathy between SR and the second wife. There were inner individual conflicts when trying to empathize toward their husbands/ wives or children because they wanted to prioritize their feelings. After some considerations emerged understanding of othersâ feelings, then emerged âif I were her/ him.â Then it happens reciprocally and continuously needs adjustment and individual acceptance process.